PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE THINK-PAIR-SHARE UNTUK MENINGKATKAN HASIL BELAJAR BAHASA INGGRIS SISWA KELAS VIII.B SMP NEGERI 1 BONDOWOSO: SMP NEGERI 1 BONDOWOSO - LILIES SURYANINGSIH (Mitra Pendidikan, 2021)
The objectives that can be conveyed in this study are to improve English learning outcomes through the application of a think-pair-share cooperative learning model for Class VIII.B students of SMP Negeri 1 Bondowoso. The research used by the author in this study is Classroom Action Research (CAR). Classroom action research can be defined as an action research carried out by the teacher as well as a researcher in the classroom or together with other people (collaboration) by designing, implementing and reflecting collaborative and participatory actions that aim to improve or improve the quality of the learning process in the classroom. class through a certain action in a cycle (Kunandar.2010). This classroom action research is carried out in the form of cyclical activities consisting of four stages in each cycle. One cycle consists of 2 meetings This research was carried out in class VIII.B of SMP Negeri 1 Bondowoso with the address at Jalan Letnan Karsono No. 3, Purbosari, Kotakulon, Kec. Bondowoso, Bondowoso Regency, Postal code 68212. This research was carried out for three months, from September to November 2018. The subjects of this school action research were class VIII.B students of SMP Negeri 1 Bondowoso in the odd semester of the 2018/2019 academic year, totaling 25 students. The data collection technique used in this study was a test. This test is intended to obtain data about student learning outcomes after being given classroom action research. Through the learning outcomes test, all the data that has been collected is then analyzed to get a clear picture of the level of success that has been achieved, while the analytical technique used in this classroom action research is a quantitative descriptive technique. Based on the results of research that has been carried out starting from the pre-cycle, Cycle I and Cycle II, it can be concluded that the application of the think-pair-share type of cooperative learning model can improve English learning outcomes for class VIII.B students of SMP Negeri 1 in the odd semester of the 2018/2019 academic year. this can be seen from: 1). Completeness Learning, from 25 the number of class VIII.B students of SMP Negeri 1 Bondowoso in the pre-cycle student learning completeness of 44.00% in the first cycle increased to 68.00% while in the second cycle it increased again to 84.00%. 2). Absorption capacity, from 25 students in class VIII.B of SMP Negeri 1 Bondowoso in the pre-cycle, the amount of absorption was 63.00, in the first cycle it increased to 69.00, while in the second cycle it increased to 76.00